Práticas de gestão de pessoas, comprometimento organizacional e seus consequentes: satisfação no trabalho e intenção de rotatividade no contexto do comércio varejista - Feitosa, Raquel Libório (2019)
In a scenario of work traversed by socioeconomic, cultural, technological and legalistic aspects, retail trade represents 47.4% of the Brazilian Gross Domestic Product, being one of the largest sources of formal labor, having, with, the highest turnover rate in the country. For these reasons, the study on People Management Practices (PGP), Organizational Commitment and its Consequent, Job Satisfaction and Intention of Turnover ocurred in retail. The research investigated how these practices influence the Commitment and how the relationship between PGP and Commitment impacts the consequent Job Satisfaction and Intention of Turnover. This quantitative, descriptive and explanatory research used a questionnaire containing demographic data and four scales, answered by 648 workers from the Fortaleza trade. The data treatment used factorial, exploratory and confirmatory analyzes, correlation and regression analyzes, and structural equation modeling. The results reinforce the studies on Normative Commitment and Continuing Commitment, and unprecedently point to the dual face of Normative Commitment and the Affective / Normative Commitment (CA / CN) profile as a motivating force to be sought. The practices Recruitment and Selection (RS); Remuneration and Rewards (RR); Training, Development and Education (TDE) and Involvement are predictors of Commitment, which in this context appears as Debt Obligation or as a Moral Duty of negative charge. The practices RS, RR and TDE positively explain Debt Obligation; and the practices SR, Engagement, and RR negatively explain Moral Duty. Commitment emerges as a predictor of Satisfaction, with the Debt Obligation factor positively explaining Satisfaction with the nature of work, promotions, and salaries. The Moral Duty factor negatively explains Satisfaction in the five dimensions. Commitment is also a predictor of Intention of Turnover, which relates negatively to Debt Obligation and positively to Moral Duty. The findings led to the dual face of the Normative Commitment, challenging retailers to increase People Management Practices that progress from Debt Obligation to one basead to the factor Moral Duty of positive charge (CA / CN profile) factor. The Commitment modeling test in the linear position did not present satisfactory indices. Throughout the analyzes, a potentiality of the Commitment as a mediator was observed. We invested in a second model and the multiple mediation analysis showed the Commitment as a mediator of the relationship between all PGP and Job Satisfaction and between all PGP and the Intention of Turnover. Satisfaction with promotions, salary, and the nature of work factors are mediated by Commitment in almost all PGP. In the scientific field, the study contributes by investigating outside the Anglo-Saxon context, in a country of collectivist culture; focus on less researched Commitment dimensions, include two consequent; using robust sample and analysis. Finally, it contributes by testing two models that articulate four constructs simultaneously. In the organizational field, it encourages the development of People Management Practices that promote Satisfaction and reduce the Intention of Turnover, through a Commitment that brings more benefits to the involved parties, and that considers cultural, socioeconomic and legal aspects of the Brazilian work context.